Accuracy of immunological tests on serum and urine for diagnosis of Taenia solium neurocysticercosis: A systematic review. - Lisa Van Acker; Luz Toribio; Mkunde Chachage; Hang Zeng; Brecht Devleesschauwer; Héctor H Garcia; Sarah Gabriël; NeuroSolve Consortium (Public Library of Science (PLoS), 2024)
Background Taenia solium neurocysticercosis is a zoonotic neglected tropical disease, for which adequate diagnostic management is paramount, especially in patients with active cysts for whom improved and timely management could prove beneficial. Immunodiagnosis can potentially partially mitigate the necessity for neuroimaging, shortening the diagnostic -and treatment- pathway. An up-to-date review of immunological test performance is however lacking. Methodology/principal findings Searches were performed in PubMed, EMBASE, Web of Science, and Scopus (up to January 2024), with included records fitting the review scope, i.e. accuracy evaluation of an antibody-/or antigen-detecting immunological test, using serum or urine of humans confirmed via reference standard (i.e. neuroimaging or surgery/biopsy). Record data was assessed, with classification of descriptive data on cyst localization and stage according to a developed confidence scale, and with selection of tests evaluated on a sufficiently high sample size. A QUADAS-2 risk of bias assessment was performed. After screening, 169 records were included for data collection, with 53 records-corresponding to 123 tests- selected for analysis. Absence of data and large data heterogeneity complicated result interpretation. The lentil lectin-bound glycoprotein enzyme-linked immunoelectrotranfser blot seems to fulfill high accuracy standards regarding detection of parenchymal active multiple cysts; also antigen-detecting tests on serum and urine performed well, additionally in detection of extraparenchymal neurocysticercosis. A novel multi-antigen print immunoassay is highly promising, with sensitivity for detection of extraparenchymal and parenchymal active single and multiple cysts of 100.0%, and specificity of 98.5%. Point-of-care tests showed promising results, however require further evaluation in targeted resource-poor settings. Conclusions/significance The review highlights the importance of transparent and unambiguous data reporting. With promising immunological tests in development, the challenge before usage in targeted settings will be to perform large-scale evaluations whilst holding into account both optimized test performance and ease of use. Accessibility to validated tests and feasibility of implementation should also be considered.